Mitigating Harmonics by using K-transformer - Zailan, Farid Haikal; Dur Muhammad Soomro (Evolution in Electrical and Electronic Engineering, 2022)
Power quality (PQ) is a general term that is commonly used to refer to uninvited disturbances in the electricity supply. One of PQ problems is harmonics. Harmonic currents affect the efficiency and reliability of the electrical supply and may pose potential safety hazards. Mitigating harmonics in the power supply is essential for delivering a stable power supply and maintaining the efficiency of all devices in the system. The first objective of this project is to investigate the PQ problem of harmonics using a conventional transformer in a test case. Then, based on the investigated harmonic problem, design a K-transformer to mitigate the harmonic problem. To achieve this objective, the test case for the harmonics problem, and mitigation technique is designed in MATLAB. Based on the result, the K-transformer is only unable to eliminate harmonic distortion (HD) on the secondary side due to simulation setup limitations for certain parameters. As a result, we added a harmonic filter bank to the secondary side of the system to mitigate all harmonics. Overall, this project demonstrated that K-transformers are effective at eliminating PQ harmonics and extending the lifespan of the transformer when compared to the conventional transformer. In order to obtain the best result for this project, one recommendation for future work is to use the different tools of simulation to fulfil the parameters of the K-transformer.